Postgrowth and Wellbeing : Challenges to Sustainable Welfare - Büchs, Milena; Koch, Max (Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
This book presents a detailed and critical discussion about how human wellbeing can be maintained and improved in a postgrowth era. It highlights the close links between economic growth, market capitalism, and the welfare state demonstrating that, in many ways, wellbeing outcomes currently depend on the growth paradigm. Here the authors argue that notions of basic human needs deserve greater emphasis in debates on postgrowth because they are more compatible with limits to growth. Drawing on theories of social practices, the book explores structural barriers to transitions to a postgrowth society, and ends with suggestions for policies and institutions that could support wellbeing in the context of postgrowth. This thought-provoking work makes a valuable contribution to debates surrounding climate change, sustainability, welfare states and inequality and will appeal to students and scholars of social policy, sociology, political science, economics, political ecology and human geography.
Keywords: Social sciences.; Social policy.; Economic growth.; Social structure.; Social inequality.; Economic sociology.; Environmental sociology.; elektronické knihy; electronic books